PENGGANTIAN ALAT PENDUKUNG REAKTOR ANAEROBIK DUA TAHAP GUNA MENINGKATKAN KUALITAS HASIL BIOGAS - Mukhtar Ghozali; Herawati Budiastuti; Alviera Wilma Fitrianie; Elis Sri Wahyuni (P3M Politeknik Negeri Indramayu, 2018)
BOD/COD ratio of leachate is 0.6 so it fulfils requirement for anaerobic treatment. Leachate is potentially to be treated, however leachate is commonly treated by aeration before it is discharged. To avoid environmental pollution and to optimize treatment, leachate can be treated anaerobically to produce biogas. Two-stage anaerobic reactors are considered to be more effective and efficient in degrading organic substances in leachate. This study aims to evaluate the reactors built to increase degradation efficiency and composition of CH4 contained in biogas. To improve reactor’s performance, the feed tank replacement, leackage check, and gas holder replacement were conducted. Leachate was obtained from Sarimukti Padalarang, West Bandung and starter, cow rumen, was obtained from a slaughter house in Ciroyom, Bandung. The value of pH in the 1st reactor (R1) was in the range of 5-6.5 and in the 2nd reactor (R2) was 7-8. Acidic pH range allows the occurrence of hydrolysis and acetogenesys, meanwhile the normal pH range allows the occurrence of methanogenesys. Analysis parameters were COD, BOD, pH, and composition of CH4 in biogas. CH4 produced within 45 days, COD degradation efficiency, and maximum CH4 composition were 2 liters, 86.9%, and 24%, respectively. CH4 was started to be produced after day 18.